2019
DOI: 10.1002/ccd.28054
|View full text |Cite
|
Sign up to set email alerts
|

Application of the DILEMMA score to improve lesion selection for invasive physiological assessment

Abstract: Objectives We sought to assess the validity of the DILEMMA score against instantaneous wave‐free ratio (iFR) and evaluate its utility in rationalizing the number of patients referred for invasive physiological assessment. Background The DILEMMA score is a validated angiographic scoring tool incorporating minimal lumen diameter, lesion length and subtended myocardial area that has been shown to predict the functional significance of lesions as assessed by fractional flow reserve (FFR). Methods Patients in the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The length of the stenosis could be an important determinant of the ΔFlow, although not statistically significant in our analysis. In this study we used QCA to quantify the severity of the proximal coronary artery lesion, although the use of an alternative angiographic scoring tool that incorporates the minimal lumen diameter, lesion length, and subtended myocardial area, such as DILEMMA score, may better predict the functional significance of lesions . Moderate proximal native coronary artery stenosis and high fractional flow reserve are known to affect the bypass graft flow due to competitive antegrade flow from the native vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the stenosis could be an important determinant of the ΔFlow, although not statistically significant in our analysis. In this study we used QCA to quantify the severity of the proximal coronary artery lesion, although the use of an alternative angiographic scoring tool that incorporates the minimal lumen diameter, lesion length, and subtended myocardial area, such as DILEMMA score, may better predict the functional significance of lesions . Moderate proximal native coronary artery stenosis and high fractional flow reserve are known to affect the bypass graft flow due to competitive antegrade flow from the native vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CPMs could be used as initial screening tools, which would enable unnecessary FFR measurements to be avoided. Indeed, a recent study showed that nearly half of intermediate lesions with a DILEMMA score of ≤2 or ≥9 could potentially have been deferred for invasive functional assessments (7). Second, CPMs can integrate more ischemia-related information than a three-dimensional vessel reconstruction, i n c l u d i n g d e m o g r a p h i c c h a r a c t e r i s t i c s , p h y s i c a l examinations, laboratory tests, and imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other types of models based on geometric reconstruction and computational fluid dynamics, CPMs cannot give a specific value of FFR but can help stratify patients or lesions that are more likely to have an abnormal FFR (see Figure 1). These CPMs may diminish the need for pressure wires and thus reduce both medical expenditure and potential complications (7). Despite an increasing number of published FFR CPMs in recent years, there has been no attempt to evaluate recent advances on this topic comprehensively.…”
Section: Introductionmentioning
confidence: 99%
“…e mechanical forces contributing to carinal shift typically occur in a single direction, making the stenosis even more eccentric and therefore exaggerating angiographic severity of the jailed SB [37]. Physiologically, the trans-stenotic pressure gradient across a lesion and therefore FFR is highly dependent on the area of myocardium subtended [38,39]. is explains the observation that, for a given stenosis and lesion length, lesions in major epicardial arteries tend to have lower FFR values than side-branch vessels by virtue of the degree of myocardium supplied [38].…”
Section: Ffr For Side Branch Assessment In Bifurcation Lesionsmentioning
confidence: 99%